My First Dinosaur board book - Dorling Kindersley, Inc.; Landis, Beth, editor (Dorling Kindersley, Inc., USA, 2002)
This colorful and durable board book introduces young children to the fascinating world of dinosaurs. Using bright, real-life photographs and simple labels, each page explores a different type of dinosaur$1 (Bhighlighting their features, behaviors, and size comparisons. Designed for toddlers and preschoolers, the book builds early vocabulary and introduces basic scientific concepts in a fun and interactive way. Published in collaboration with the American Museum of Natural History.s
Meet the dinosaurs -- Big and small -- The meat eaters -- The plant eaters -- Spikes and horns -- Dinosaurs with armour -- Fast and fierce -- Dinosaur babies.
Includes labelled photographs and simple descriptions for each dinosaur. Published in association with the American Museum of Natural History.
1 - 3 years
Text in English.
Keywords: Dinosaurs: Juvenile literature: Board books